Historical Study of the Role of the Majlis Tafsir Al-Qur’an Foundation (MTA) Deli Serdang, Nourth Sumatra 1996-2023 - Nisa, Fitri Khoirun; Achiriah, Achiriah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This article discusses the history, development and role of the Majlis Tafsir Al-Qur'an Foundation in Deli Serdang Regency, North Sumatra, 1996-2023. The aim of this research is to answer the problem formulation related to the history, development and role of the Majlis Tafsir Al-Qur'an Foundation. The method used in this research is a qualitative research method using a diachronic approach. Collection techniques are carried out by observation, interviews and documentation. This research was carried out in the stages of heuristics, source criticism, interpretation and historiography. The results of this research show that the Majlis Tafsir Al-Qur'an Deli Serdang Foundation, North Sumatra was founded in 1996 and was pioneered by 6 migrants from the island of Java. Development of the Deli Serdang Representative MTA Foundation, North Sumatra from 1996-2023, there are 13 Representatives and 10 Branches spread across the North Sumatra region. The role of the MTA Foundation, Representative of Deli Serdang, North Sumatra, can be seen from the activities which are carried out well as a result of the collaboration of all congregations with the community and related agencies.